Influence of radiation-induced defects on CdTe and CdZnTe detectors properties - Kondrik, A.I. (Вопросы атомной науки и техники, 2015)
The correlation between radiation-induced defects, arising in CdTe:Cl and CdZnTe after the hard X-ray irradiation, and charges collection efficiency of detectors based on these materials has been investigated by means of computer simulation method. The role of radiation-induced defects during degradation of CdTe:Cl detector performance has been determined. An attempt to explain the reasons for higher radiation resistance of CdZnTe compared with CdTe:Cl has been made. Методом компьютерного моделирования проведено исследование корреляции между радиационными дефектами, возникшими в CdTe:Cl и CdZnTe после жесткого рентгеновского облучения, и эффективностью сбора зарядов детекторов на их основе. Определена роль радиационных дефектов в процессах деградации детекторных характеристик CdTe:Cl. Сделана попытка объяснить причины более высокой радиационной стойкости CdZnTe по сравнению с CdTe:Cl. Методом комп’ютерного моделювання проведено дослідження кореляції між радіаційними дефектами, які виникли в CdTe:Cl та CdTe після жорсткого радіаційного опромінення, і ефективністю збору зарядів детекторів на їх основі. Визначена роль радіаційних дефектів у процесах деградації детекторних характеристик CdTe:Cl. Зроблена спроба пояснити причини більш високої радіаційної стійкості CdZnTe у порівнянні з CdTe:Cl.